Sekuen Gena Penyandi Protein L1 Human Papilloma Virus 16 dan 18 Dari Penderita Karsinoma Serviks di RSUP DR. Sardjito, Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
ABSTRACT At present, cervical carcinoma became the most frequent carcinoma found in Indonesia. It was estimated that cervical carcinoma patients reached 100-180 every 100.000 population. According to the epidemiologic data, there was strong association between cervical carcinoma and Human Papilloma Virus (HPV), especially HPV-16 and HPV-18. LI gene of HPV coded major capsid protein that was responsible for viral-host interaction. Protein LI now became the target of prophylaxis vaccine against papilloma virus. Intratype variants of certain HPVwhich could be detected in LI gene, were common around the world. The problem of the study was the nucleotides sequences of LI gene of Human Papilloma Virus -16 and -18 had not been explored yet in Indonesia, especially from Yogyakarta. The confirmation of the nucleotides sequences would be important in the development of specific prophylactic vaccine in the future. The objective of the study was to define the nucleotides sequences of LI gene of Human Papilloma Virus -16 and -18 from Cervical Carcinoma patients from Dr. Sardjito hospital, Yogyakarta, Indonesia. Total DNA were obtained from cervical tissue biopsy of Cervical Carcinoma patients. The total DNA were then amplified by Polymerase Chain Reaction method using sets of primers to amplify the LI gene of HPV-16 and HPV-18. Analysis of PCR products indicated bands thought to be similar with the desired base pair length. Direct sequencing with automated sequencer ABI PRISM 377 were then applied to the PCR products. Analysis of the nucleotides sequences of the LI gene of HPV-16 from a patient with cervical carcinoma indicated a polymorphism with differences in nucleotides from (1) A -> G at position 6434 (causing a difference at amino acid level from tyrosin to arginin position 266), (2) T -> G at position 6690 (causing a difference at amino acid level from serine to alanin at position 391) and (3) C -> T at position 6826. It could also be used for VLP production and coded all amino acids participated in H16.V5 and H16.E70 epitopes that could induce potent neutralizing antibodies. Analysis of the necleotides sequences of the L1 gene of HPV-18 from a patient with cervical carcinoma indicated a polymorphism eith differences in nucleotides from (1) C -> G at position 5701 (sause a differenceat amino acid level from P -> A), (2) G -> A at position 6323 (cause a difference at amino acid level from M -> I), (3) C -> G at position 6460 (cause a difference at amino acid level from P -> R), (4) C -> G at position 6625 (sause a difference at amino acid level from P -> R), (%) C -> G at position 6842, and (6) G -> A at position 7022